Wall Street’s bailout bet: Market reactions to house price releases in the presence of bailout expectations - Löffler, Gunter; Posch, Peter N (Journal of Banking & Finance, 2013)
The rise and subsequent collapse of US house prices was one of the factors underlying the recent financial crisis. One could expect that the crisis brought increased attention to the housing market and thus led to stronger market reactions to house price news. We find that reactions indeed change, but with a peculiar twist: from September 2008 on, good news from the housing market are associated with falling US stock prices, and vice versa. The likely explanation, for which we provide cross-sectional evidence, is that falling house prices increased the market’s trust in a government bailout, thereby increasing market valuations of firms that were expected to benefit from government rescue measures.